Calculation of magnetic force and torque between two arbitrarily oriented circular filaments using Kalantarov–Zeitlin's method. (15th April 2022) - Poletkin, Kirill V.
Abstract: In this article, formulas for calculation of magnetic force and torque between two circular filaments arbitrarily oriented in space were derived by using Kalantarov–Zeitlin's method. Formulas are presented in an analytical form through integral expressions, whose kernel function is expressed in terms of the elliptic integrals of the first and second kinds, and provide an alternative formulation to Babič's expressions. The derived new formulas were validated via comparison with a series of reference examples. Also, we obtained additional expressions for calculation of force and torque between two circular filaments by means of differentiation of Grover's formula for the mutual inductance between two circular filaments with respect to appropriate coordinates. These additional expressions allow to verifying comprehensively and independently derived new formulas. Graphical abstract: Highlights: A set of formulas for calculation of magnetic force and torque were derived. Formulas are presented in an analytical form through integral expressions. Formulas were derived by using Kalantarov-Zeitlin's method.